A qualitative study identifying the cost categories associated with electronic health record implementation in the UK. (12th February 2014) - Slight, Sarah P; Quinn, Casey; Avery, Anthony J; Bates, David W; Sheikh, Aziz
Abstract: Objective We conducted a prospective evaluation of different forms of electronic health record (EHR) systems to better understand the costs incurred during implementation and the factors that can influence these costs. Methods We selected a range of diverse organizations across three different geographical areas in England that were at different stages of implementing three centrally procured applications, that is, iSOFT's Lorenzo Regional Care, Cerner's Millennium, and CSE's RiO. 41 semi-structured interviews were conducted with hospital staff, members of the implementation team, and those involved in the implementation at a national level. Results Four main overarching cost categories were identified: infrastructure (eg, hardware and software), personnel (eg, training team), estates/facilities (eg, space), and other (eg, training materials). Many factors were felt to impact on these costs, with different hospitals choosing varying amounts and types of infrastructure, diverse training approaches for staff, and different software applications to integrate with the new system. Conclusions Improving the quality and safety of patient care through EHR adoption is a priority area for UK and US governments and policy makers worldwide. With cost considered one of the most significant barriers, it is important for hospitals and governments to be clear from the outset of the major cost categories involved and the factors that may impact on these costs. Failure to adequately train staff or to follow key steps in implementation has preceded many of the failures in this domain, which can create new safety hazards.